2013
DOI: 10.1055/s-0033-1333752
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress after a Carbohydrate Meal Contributes to the Deterioration of Diastolic Cardiac Function in Nonhypertensive Insulin-treated Patients with Moderately Well Controlled Type 2 Diabetes

Abstract: The prevalence and prognostic importance of diastolic dysfunction in type 2 diabetes has only recently been appreciated. We tested the hypothesis that in insulin treated type 2 diabetes (D), carbohydrate consumption induces oxidative stress resulting in further impairment of diastolic function beyond structural myocardial stiffness. The effects of a pure carbohydrate breakfast (48 g) on oxidative stress and cardiac function were studied in the fasting and postmeal states in subjects without hypertension or ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
0
13
2
Order By: Relevance
“…The observed postprandial increase in diastolic workload in both type 2 diabetes and healthy overweight individuals is novel. Our data contrast the few previous studies that investigated the effects of lipid infusions or a carbohydrate rich meal on cardiac function [ 9 , 10 ]. Further study is needed to determine whether this is a result of the “combined meal” used here.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The observed postprandial increase in diastolic workload in both type 2 diabetes and healthy overweight individuals is novel. Our data contrast the few previous studies that investigated the effects of lipid infusions or a carbohydrate rich meal on cardiac function [ 9 , 10 ]. Further study is needed to determine whether this is a result of the “combined meal” used here.…”
Section: Discussioncontrasting
confidence: 99%
“…Although few studies have investigated the acute effects of fast food on cardiac function, it is observed that food-induced elevation of circulating glucose and oxidative stress reduce diastolic function in insulin-treated type 2 diabetes patients [ 9 ], and that acute elevations in circulating triglycerides yield compensatory increases in systolic function of the left ventricle in healthy individuals [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study performed with the same team [22], it was revealed that maltodextrin and dextrose given at the dose of 2.25 gr/kg had no effects on TAG, malondialdehyde, hydrogen peroxide, nitrate/nitrite and trolox-equalant antioxidant capacity measured at baseline, 1st, 2nd, 4th and 6th hours. However, in another study where the effects of 48 gr of glucose loading along with subcutaneous insulin on OS and cardiac functions were investigated in 21 diabetic patients and 20 controls nearly at the age of 60 years, Bibra et al [23] reported that when OS was measured with nitrothyrosine, OS levels were similar in diabetic patients to those found in controls, but nitrotyrosine levels became increased after loading glucose to patients with DM. In the same study, nitrotyrosine levels were shown to increase from 3.6 to 3.8 nMol/l in diabetics while decreasing from 3.4 to 3 nMol/l in controls, and we considered that the difference could arise from the decrease in controls rather than the increase seen in diabetics.…”
Section: Pcos Polycystic Ovary Syndrome Tos Total Oxidant Status Tamentioning
confidence: 99%
“…The reduction in OS by antioxidants may display favor effects on the development of CVDs [19]. In the literature, many studies with controversial results report that macronutrients, such as carbohydrates, triglyceride and protein have a developmental effect on OS in different populations of patients [20][21][22][23][24][25][26]. Oral glucose tolerance test is frequently used in daily practice for detecting DM or gestational DM.…”
Section: Introductionmentioning
confidence: 99%
“…Endocrine Care overproduction of free radicals and reactive oxygen species (ROS), which in turn play an important role in precipitating diabetic vascular disease [6][7][8].…”
mentioning
confidence: 99%